2015
DOI: 10.1242/bio.010215
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate rapidly remodels PAP85-120, SEM1(45-107), and SEM2(49-107) seminal amyloid fibrils

Abstract: Semen harbors amyloid fibrils formed by proteolytic fragments of prostatic acid phosphatase (PAP248-286 and PAP85-120) and semenogelins (SEM1 and SEM2) that potently enhance HIV infectivity. Amyloid but not soluble forms of these peptides enhance HIV infection. Thus, agents that remodel these amyloid fibrils could prevent HIV transmission. Here, we confirm that the green tea polyphenol, epigallocatechin-3-gallate (EGCG), slowly remodels fibrils formed by PAP248-286 termed SEVI (semen derived enhancer of viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…In 2015, Castellano et al [36] investigated the anti-SEVI activity of EGCG ( 1 ) in greater detail. They confirmed that 1 can remodel all four classes of seminal amyloid, PAP248–286, PAP85–120, SEM1(45–107), and SEM2(49–107) at 200 μM and the viral infectivity was reduced to ~61%, ~35%, and 11% at 0.25 μM against the HIV-1 strain BL2, Bal, and 89.6, respectively.…”
Section: Antiviral Activity Of Catechins On Enveloped (−) Rna Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Castellano et al [36] investigated the anti-SEVI activity of EGCG ( 1 ) in greater detail. They confirmed that 1 can remodel all four classes of seminal amyloid, PAP248–286, PAP85–120, SEM1(45–107), and SEM2(49–107) at 200 μM and the viral infectivity was reduced to ~61%, ~35%, and 11% at 0.25 μM against the HIV-1 strain BL2, Bal, and 89.6, respectively.…”
Section: Antiviral Activity Of Catechins On Enveloped (−) Rna Virusmentioning
confidence: 99%
“…Regarding these biological properties, EGCG ( 1 ) has been reported to possess a broad spectrum of antiviral activities against DNA viruses such as herpes simplex virus (HSV; Herpesviridae ) [5,6,7,8,9,10,11], adenovirus ( Adenoviridae ) [10,12], human papilloma virus (HPV; Papovaviridae ) [13], and hepatitis B virus (HBV; Hepadnaviridae ) [14], and against (+)-RNA viruses such as hepatitis C virus (HCV; Flaviviridae ) [10,15,16,17,18,19], Zika virus (ZIKV; Flaviviridae ) [20,21,22,23], dengue virus (DENV; Flaviviridae ) [23,24], West Nile viruses (WNV; Flaviviridae ) [23], Chikungunya virus (CHIKV; Togaviridae ) [25], and Porcine Reproductive and Respiratory virus (PRRS; Atteriviridae ) [26], and (−)-RNA viruses such as human immunodeficiency virus (HIV; Retroviridae ) [27,28,29,30,31,32,33,34,35,36], Ebola virus (EBOV; Filoviridae ) [37] and influenza virus ( Orthomyxoviridae ) [2,10,38,39,40,41,42,43,44,45,46,47,48]. …”
Section: Introductionmentioning
confidence: 99%
“…As a polyphenolic compound found in green tea, EGCG has the ability to degrade the amyloid fibrils of human SEVI and block human SEVI-mediated HIV enhancement 6,3941 . We showed here that EGCG could also degrade macaque SEVI-formed amyloid fibrils (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy is to define ATP-independent protein disaggregases, which may couple binding energy to disaggregation and are operational outside cells. Select small molecules, including CLR01, a lysine- and arginine-specific molecular tweezer, and the green tea polyphenol, EGCG, can safely disaggregate or remodel diverse amyloids [57,58,59••,60]. A human Aβ oligomer- and fibril-specific monoclonal antibody, aducanumab, promotes clearance of Aβ plaques and may retard clinical decline in AD patients and is now in phase 3 trials [61••].…”
Section: Gene 3 Protein a Protein Disaggregase From Bacteriophage M13mentioning
confidence: 99%